Dysmenorrhea due to undiagnosed obstructed hemi-vagina and ipsilateral renal anomaly syndrome can become a cause of suicide - Akari Takaya Uno; Ken-ichi Mukaisho; Masahito Hitosugi (Komiyama Printing Co. Ltd, 2022)
Background: A Japanese woman in her early twenties had committed suicide, jumped from a 25-meter high bridge into a lake. She had been suffering from severe dysmenorrhea and general fatigue monthly. Results: A forensic autopsy revealed indications of a bicorporeal uterus, obstructed hemi-vagina, and ipsilateral renal agenesis, which lead to a diagnosis of obstructed hemi-vagina and ipsilateral renal anomaly (OHVIRA) syndrome. On the right side of the uterus, an enclosed cavity composed of black clots was observed. Histological findings suggested that her endometrium was in the early proliferative phase, implying that she was in the menstrual phase just before her death. She may have been suffering from severe lower abdominal pain from the increased pressure of the closed uterus cavity. Conclusions: This case indicates that dysmenorrhea from undiagnosed OHVIRA syndrome can possibly lead to a suicide attempt. In Japan, because suicide was the leading cause of death for people aged 15 to 39 in 2019, preventive measures for suicide should be promoted. The present case also suggests that intervention for dysmenorrhea may prevent this in adolescent woman.